Performance of Self-Compacting Concrete Containing Pozzolanic Materials in Aggressive Environment - L.A. Zghair; Q.J. Frayyeh; M.M. Salman (Engineering and Technology Journal, 2017)
The aims of this study is to investigate the resistance of different SCC mixtures to aggressive solutions. The investigation included the type of the cementitious materials (silica fume and high reactivity Attapulguite-HRA) and limestone powder (chalk powder and Al-gubra). The powder content of the mixes was kept constant, 500 kg/m3. The slump flow, L-box, and V-funnel were performed for mixes in there fresh state. In the present work, the specimens were immersed in sulfuric acid solution with a concentration of 0. 5% up to 289 days after normal curing for 28 days. After concrete has hardened, two types of test are performed. Firstly, destructive tests are conducted including (compressive strength, splitting tensile strength, and modulus of rupture). Secondly, a mass loss as non-destructive test is performed. The results obtained from this work, show that concrete mixes with chalk powder only, had the best resistance to sulfuric acid solution comparable with concrete made with Pozzolanic materials the reduction in compressive strength was 25. 9 %. In addition, concrete mixes with HRA had the worst resistance.